Agaricus Blazei Hot Water Extract Shows Anti Quorum Sensing Activity in the Nosocomial Human Pathogen Pseudomonas Aeruginosa - Marina Soković (Molecules, 2014)
The edible mushroom Agaricus blazei Murill is known to induce protective immunomodulatory action against a variety of infectious diseases. In the present study we report potential anti-quorum sensing properties of A. blazei hot water extract. Quorum sensing (QS) plays an important role in virulence, biofilm formation and survival of many pathogenic bacteria, including the Gram negative Pseudomonas aeruginosa, and is considered as a novel and promising target for anti-infectious agents. In this study, the effect of the sub-MICs of Agaricus blazei water extract on QS regulated virulence factors and biofilm formation was evaluated against P. aeruginosa PAO1. Sub-MIC concentrations of the extract which did not kill P. aeruginosa nor inhibited its growth, demonstrated a statistically significant reduction of virulence factors of P. aeruginosa, such as pyocyanin production, twitching and swimming motility. The biofilm forming capability of P. aeruginosa was also reduced in a concentration-dependent manner at sub-MIC values. Water extract of A. blazei is a promising source of antiquorum sensing and antibacterial compounds.